Diaspora identities through folk dance. A cyber-anthropological study - Sigl, Eveline (2011)
Parting from the reality of diasporic communities of Bolivian migrants the present article explores what people communicate within the Web 2.0 and using Web 2.0 technologies. It is a cyber-anthropological study researching the implications Bolivian folk dance has for the Bolivian migrants and their descendants, especially focussing on issues of identity and ethnicity.